Упростить выражение ** фото

0 голосов
29 просмотров

Упростить выражение на фото


image

Алгебра (42 баллов) | 29 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

(а-12с)/(а²-16с²) + 4с/(а²-4ас) = (а-12с)/((а-4с)(а+4с)) + 4с/(а(а-4с)) = 
= (а²-12ас+4ас+16с²)/(а(а-4с)(а+4с)) = (а-4с)²/(а(а-4с)(а+4с)) = 
= (а-4с)/(а(а+4с))

(98.6k баллов)
0 голосов

(a-12c)/(a-4c)(a+4c)+4c/a(a-4c)=[a(a-12c)+4c(a=4c)]/[a(a-4c)(a+4c)]=
=a²-12ac+4ac+16c²)/[a(a-4c)(a+4c)]=(a²-8ac+16c²)/[a(a-4c)(a+4c)]=
=(a-4c)²/[a(a-4c)(a+4c)]=(a-4c)/(a²+4ac)

(750k баллов)